BIOCHEMICAL PROFILE IN TRYPANOSOMIASIS OF DOGS - Rode, A M; Bijwal, D L; Chopde, S S; Shrikhande, G B (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Trypanosomiasis was created by inoculating trypanosome infected blood subcutaneously. Two groups were formed each with six dogs. One group served as untreated control, while the dogs from other group received treatment with Diaminazene aceturate. Biochemical estimation of blood were carried out on 0, 3rd, 7th and 15th days respectively in both the groups. The biochemical estimation reveled hypoglycemia, hypoprotenaemia, hypoalbuminia, decrease in A:G ratio with increase in AST and ALT in the present study.